2019
DOI: 10.1051/e3sconf/20199404003
|View full text |Cite
|
Sign up to set email alerts
|

Study of Digital Elevation Model (DEM) Extraction using Stereo Radargrammetry TerraSAR-X in Madiun Area – Elevation Accuracy Improvement

Abstract: High resolution images data from Terrasar-X are used to extract digital elevation model (DEM) using stereo radargrammetry in the attempt to achieve better resolution of terrain surface in Indonesia. As sample in this study, stereo pairs images from TerraSAR-X StripMap mode (~3m resolution) on Madiun city is used with difference of incidence angle around ~18.88 degree to extract the elevation of the area. Furthermore, field observation on the selected area will be used on elevation accuracy assessment. The digi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…As a result, several investigations on DEM have been conducted by researchers leading to many methodical propositions to reduce errors and increase accuracy. For example, Yue et al (2007), Cook et al (2012), Wilson (2012), Sari et al (2019), Hugenholtz et al (2013), Chen and Yue (2010), Warriner (2005), and Zhou et al (2012) suggested different methods for generating improved DEM. Further, DEM accuracy was evaluated by Hawker et al (2019) over Croatia.…”
Section: Background and Related Workmentioning
confidence: 99%
“…As a result, several investigations on DEM have been conducted by researchers leading to many methodical propositions to reduce errors and increase accuracy. For example, Yue et al (2007), Cook et al (2012), Wilson (2012), Sari et al (2019), Hugenholtz et al (2013), Chen and Yue (2010), Warriner (2005), and Zhou et al (2012) suggested different methods for generating improved DEM. Further, DEM accuracy was evaluated by Hawker et al (2019) over Croatia.…”
Section: Background and Related Workmentioning
confidence: 99%
“…In this paper, a new type of neural network that directly processes point clouds is used. It respects the invariance of the arrangement of input points and divides the tree point clouds [37].…”
Section: Point Cloud Segmentation Algorithmmentioning
confidence: 99%